THE EFFECT OF GIVING rGH HORMONE, THYROXINE AND ITS COMBINATIONS ON THE GROWTH AND SURVIVAL RATE OF GURAMI LARVAE (Osphronemus gouramyLac.) - Lifia Desi; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTGiving the rGH hormone, thyroxine hormone (T4) and its combination through the immersion method in NaCl 0,9 %. The research was done on January - March 2020 at Fish Hatchery and Breeding Laboratory, Aquaculture major, Faculty of Fisheries, Riau University. This research aims to determine the effect of giving rGH hormone, thyroxine hormone (T4) and their combinations, to the growth and the survival rate of gourami larvae. The method this research was used on experimentwith one-factor randomized design with four treatments and three replications. The treatments used are : P1 = Control, P2 = rGH 7 mg/L, P3 = T4 0.75 m/L, P4 = combination of rGH 7 mg/L and rGH 7 mg/L. Based on the research, the best treatment was on P4 (the combination of rGH 7 mg/L dose and thyroxine 0.75 mg/L dose) with results absolute weight growth: 1.34 g, absolute length growth: 3.8 cm, specific growth rate: 12, 3% and survival rate of fish : 98%. The quality of the water during this research was intemperature 26.1-27.4 C, pH 6.6-7.3 and dissolved oxygen 4.3-6.5 mg/L, it still supports the optimal fish growth for gouramy larvae. Keywords: rGH, Thyrokxine, Combination,Osphronemus gouramyLac.